Instagram @Bolalobfutsal Sebagai Media Sosial Informasi Olahraga pada Kompetisi Liga Futsal Profesional Indonesia Tahun 2023 Periode Januari - Muhammad Ananda Perdana; Made Pramono (Journal of Creative Student Research, 2024)
Instagram is a medium that can be used to disseminate information, especially information about futsal, such as the Instagram account @bolalobfutsal. The 2023 Indonesia Professional League competition is one of the most frequently published futsal news on this account. This study aims to understand how Instagram social media functions for the benefit of Instagram users, especially those who follow the @bolalobfutsal account. By using surveys or questionnaires, this research uses a quantitative approach. The number of samples needed for a sample of 100 respondents is determined using saturated sampling, which is based on the Taro Yamane calculation formula or the calculation approach. Respondents are those who follow @bolalobfutsal on Instagram. Through Instagram Story, surveys are distributed to account followers to collect data. A positive and substantial relationship between the function of the Instagram social media account @bolalobfutsal as a channel for disseminating sports news that is of interest to followers and readers of futsal sports news can be seen by applying a descriptive data analysis approach. The findings of this study can provide a broad picture of the function of social media platforms such as Instagram as a channel for sports news readers through the Instagram account @bolalobfutsal. This the account manager is expected to be able to maintain informative uploads because Instagram is a tool that can publishes news information about futsal, including the 2023 Indonesian Professional League competition.